Study on Physiological Changes of Seed Broccoli under Salt Stress. Issue 1 (March 2021) - Zhou, Yong; Peng, Yanjie; Liu, Zhong; Huang, Jiao; Zheng, Ying; Wang, Yu
Abstract: In this paper, the typical neutral salt NaCl in salt soil was used to simulate salt stress. The changes of CAT, H2 O2, POD, proline, total SOD and leaf thickness of H17, a seed broccoli variety, under the concentration of 100, 200 and 300 mmol/L NaCl were detected at water sensitive stage of seed broccoli. The results showed that the total SOD activity of seed broccoli was not significantly affected, and the activity of POD was more sensitive to low salt stress (100 mmoml/L). The activity of POD remained basically stable when the salt concentration continued to increase. The activity of CAT showed a tendency to decrease first and then rise. The H2 O2 and proline exhibited more sensitive to low and moderate salt concentration with a trend of rise first and fall then. The content of H2 O2 and proline reached the peak at middle salt concentration (200 mmol/L). Additionally, the leaf thickness was positively correlated with salt stress concentration.